Analisis Makna Dalam Lirik Single-Single Lagu Karya Soegi Bornean - Amalia, Ineu Tuting; Agustiani, Tanti (Universitas Islam Sumatera Utara, 2024)
Semiotics is the study of signs (sign). According to Ferdinand De Saussure's semiotic theory, the most important subject of Saussure's theory is the principle that language is a system of signs, and each sign is composed of two parts, namely the signifier and the signified. This study focuses on analyzing the meaning contained in the song lyrics of Soegi Bornean's singles entitled